Guidance to 2018 good practice: ARIA digitally‐enabled, integrated, person‐centred care for rhinitis and asthma. Issue 1 (11th March 2019) - Bousquet, J.; Bedbrook, A.; Czarlewski, W.; Onorato, G. L.; Arnavielhe, S.; Laune, D.; Mathieu‐Dupas, E.; Fonseca, J.; Costa, E.; Lourenço, O.; Morais‐Almeida, M.; Todo‐Bom, A.; et al.
Abstract: Aims: Mobile Airways Sentinel NetworK (MASK) belongs to the Fondation Partenariale MACVIA‐LR of Montpellier, France and aims to provide an active and healthy life to rhinitis sufferers and to those with asthma multimorbidity across the life cycle, whatever their gender or socio‐economic status, in order to reduce health and social inequities incurred by the disease and to improve the digital transformation of health and care. The ultimate goal is to change the management strategy in chronic diseases. Methods: MASK implements ICT technologies for individualized and predictive medicine to develop novel care pathways by a multi‐disciplinary group centred around the patients. Stakeholders: Include patients, health care professionals (pharmacists and physicians), authorities, patient's associations, private and public sectors. Results: MASK is deployed in 23 countries and 17 languages. 26, 000 users have registered. EU grants (2018): MASK is participating in EU projects (POLLAR: impact of air POLLution in Asthma and Rhinitis, EIT Health, DigitalHealthEurope, Euriphi and Vigour). Lessons learnt: (i) Adherence to treatment is the major problem of allergic disease, (ii) Self‐management strategies should be considerably expanded (behavioural), (iii) Change management is essential in allergic diseases, (iv) Education strategies should be reconsidered using a patient‐centred approach and (v) Lessons learnt for allergic diseases can be expanded to chronic diseases.